2013
DOI: 10.1007/s11033-013-2554-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of vascular endothelial growth factor and risk for retinopathy of prematurity in South of Iran

Abstract: Retinopathy of prematurity (ROP) is a multifactorial disease, that cause visual impairment in premature children. The exact pathogenesis and etiology of ROP is unknown and genetic susceptibility is considered as risk factor. Vascular endothelial growth factor (VEGF) plays a major role in retinal neovascularization and subsequently retinal detachment. VEGF polymorphism is associated with proliferative ROP in some studies. We examined the possible association of the VEGF gene polymorphisms with ROP in preterm in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Genetic association studies with ROP and VEGF gene have been contradictory. 15,33,87,99,142,176,197,206,222,223,305,339,343,381 The Wnt signaling pathway genes previously identified in familial exudative vitreoretinopathy, including FZD4 and LRP5 , and Norrie Disease Protein (NDP) gene have also been explored with positive associations with ROP including stage 4/5 ROP in several studies; 90,97,104,172,173,218,244,342 however, there have been only a few genetic studies with adequate sample size and refined inclusion criteria. A large genetic cohort study identified SNPs in the intronic region of brain-derived neurotrophic factor (BDNF) gene as associated with treatment-requiring ROP, which warrants further studies on functional effects of intronic variants of BDNF and replication studies.…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…Genetic association studies with ROP and VEGF gene have been contradictory. 15,33,87,99,142,176,197,206,222,223,305,339,343,381 The Wnt signaling pathway genes previously identified in familial exudative vitreoretinopathy, including FZD4 and LRP5 , and Norrie Disease Protein (NDP) gene have also been explored with positive associations with ROP including stage 4/5 ROP in several studies; 90,97,104,172,173,218,244,342 however, there have been only a few genetic studies with adequate sample size and refined inclusion criteria. A large genetic cohort study identified SNPs in the intronic region of brain-derived neurotrophic factor (BDNF) gene as associated with treatment-requiring ROP, which warrants further studies on functional effects of intronic variants of BDNF and replication studies.…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…In the retina of premature babies, vascularization is achieved through angiogenesis and the proliferation of endothelial cells. This proliferation occurs under the influence of VEGF, which is critical for retinal vascular development [ 92 , 93 ], and the genetic expression of VEGF has an essential role. Retinal hypoxia is associated with a marked increase in VEGF expression.…”
Section: Resultsmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) in the VEGF −460 T/C (rs833061) and +936 C/T (rs3025039) in the respective 5′ and 3′ untranslated region (UTR) have been reported in different populations 3 . Some studies have found association of VEGF −460 T/C or +936 C/T polymorphism with ROP risk,4, 5, 6 but some other studies show no association between VEGF −460 T/C or +936 C/T polymorphism and risk of ROP 7, 8, 9, 10, 11. These studies revealed a conflicting conclusion, probably due to the relatively small size of subjects, since individual studies are usually underpowered in detecting the effect of low penetrance genes.…”
Section: Introductionmentioning
confidence: 99%